2022
DOI: 10.1182/bloodadvances.2021005745
|View full text |Cite
|
Sign up to set email alerts
|

Nonneutralizing FVIII-specific antibody signatures in patients with hemophilia A and in healthy donors

Abstract: Previous studies identified nonneutralizing FVIII-specific antibodies in the circulation of severe and non-severe hemophilia A patients without FVIII inhibitors and also in some healthy individuals. To gain a better understanding of the nature of these nonneutralizing antibody responses, we analyzed and compared anti-FVIII antibody signatures in three study cohorts - previously treated severe as well as non-severe hemophilia A patients without FVIII inhibitors, and healthy donors. FVIII-binding IgM, IgG1-4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 75 publications
(115 reference statements)
1
12
0
Order By: Relevance
“…Indeed, 1 BU/mL only showed a borderline result when spiked into plasma NP #1. On the other hand, however, plasma NP #2 showed a positive result also for the unspiked sample, most probably reflecting the well‐known presence of non‐neutralizing FVIII‐specific antibodies in healthy individuals 21 . Further FVIII‐spiking studies showed only marginal impact of FVIII at levels around 0.15 IU/mL (Figure S1).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, 1 BU/mL only showed a borderline result when spiked into plasma NP #1. On the other hand, however, plasma NP #2 showed a positive result also for the unspiked sample, most probably reflecting the well‐known presence of non‐neutralizing FVIII‐specific antibodies in healthy individuals 21 . Further FVIII‐spiking studies showed only marginal impact of FVIII at levels around 0.15 IU/mL (Figure S1).…”
Section: Resultsmentioning
confidence: 93%
“…Indeed, such a strategy would address the described presence of low-titer non-inhibitory FVIII-antibodies in healthy individuals. 21,25 In order to standardize the detection of FVIII-bAb, determination of SCPs for the FVIII-bAb assay was done at both sites. In this regard, the specificity was pre-defined as 95%, necessitating the need for a confirmatory assay setting whose specificity was set to 99.9%, yielding a 0.1% false positive rate for the final sample results.…”
Section: Fviii-bab Assaymentioning
confidence: 99%
“…26 Another limitation of the study is that no detection of IgG subclasses was performed as in the recent publication by Schweiger et al since this was not the aim of the current study. 27 All methods were not performed in all samples and especially CBA results were lacking and could not be performed due to lack of sample, since the amount of plasma needed for xFLI and ELISA is much smaller.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize that non-inhibitory anti-FVIII antibodies can also be present in patients with hemophilia A and even in healthy individuals [ 11 , 12 ]. For some hemophilia A patients, these non-inhibitory antibodies can influence the half-life of FVIII in circulation [ 13 ] and impact the efficacy of replacement therapy, although to a smaller magnitude.…”
Section: The Development Of Anti-factor VIII Neutralizing Antibodies ...mentioning
confidence: 99%